LITERATURE RIVIEW TOKSIKOLOGI LIMBAH B3 PUSKESMAS - Linda Haryani; Herniwanti; Marwad (Journal of Hospital Administration and Management (JHAM), 2026)
The management of hazardous and toxic (B3) solid waste in Primary Health Care Centers (Puskesmas) remains a critical issue due to its potential to cause harmful biological and chemical exposure to health workers, the community, and the environment. This study aims to analyze toxicological risks and management challenges of B3 solid waste in Primary Health Care Centers based on a review of recent literature. The research employed a literature review method with a descriptive qualitative approach, involving a search of nationally indexed and international journals published between 2020 and 2025; article selection based on inclusion and exclusion criteria; and thematic extraction and analysis of eight relevant publications from the Riau region and comparative areas. Data analysis covered waste characteristics, human resources, facilities and infrastructure, and policy aspects. The review results indicate that infectious waste and sharps constitute the largest fractions of B3 solid waste generated by Primary Health Care Centers. Major issues include improper waste segregation, non-standard temporary storage facilities, limited availability of trained human resources, and dependence on third-party waste handlers. Identified toxicological risks include potential infections from needle-stick injuries, exposure to heavy metals and pharmaceutical residues, and environmental contamination that adversely affects public health. Overall, the studies reveal that the primary problem lies in weak implementation of standard operating procedures despite the existence of national regulations. This study concludes that strengthening human resource capacity, providing adequate infrastructure, ensuring compliance with technical standards, and implementing risk management based on toxicological principles are key strategies to improve safety and the quality of B3 solid waste management in Primary Health Care Centers.